Seeing through infrastructure: Ethnographies of HealthIT, Development Aid, Energy and Big Tech - Ross Winthereik , Brit (STS Encounters, 2018)
Inaugural professorial lecture From the introduction: It is a pleasure and a great privilege to be standing here in front of you today to celebrate the newly established chair in Science and Technology Studies and ethnography at the IT University of Copenhagen. I am excited that so many have come to spend the afternoon here. Science and Technology Studies or STS is a relatively new academic field. It is the study of how social, political and cultural values affect scientific research and technological innovation and vice versa, that is how scientific and technological developments affect societal values and politics in turn. Questions of interest to this field have for example been: What makes scientific facts credible? What makes us trust in science? How to create civic engagement around questions of science and technology? How is the general public involved in decisions around for example the manipulation of genes or the location of nuclear waste storage?